Development of LKS With a STEM Approach that Supports The Mathematical Communication Skills of SMP Students - Novaliyosi, Novaliyosi; Khaerunnisa, Etika; Khasanah, Mufidatun (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
The research was motivated by low mathematical communication skills of students and the lack of variety of teaching materials that can equip students to face the challenges of the 21st century including load activities to support mathematical communication skills. Based on these, this research aims to: (1) produce mathematics students worksheets (LKS) with STEM approach that supports mathematical communication skills of junior high school student and suitable for use in the mathematics learning. This development research was carried out by adopting the ADDIE Research Development model. The results showed that: (1) Mathematics Student Worksheets with the STEM (Science, Technology and Engineering and Mathematics) Approach that Supported Junior High School Students Mathematical Communication Skills that were feasible were used in terms of validation test results by experts with a percentage of eligibility reaching 84.77% is at the interval   4.20 which is 4.23 with the category very good; and the quality of worksheets based on student and teacher responses shows the criteria of practical with a percentage value of them are 75% and 85%.Penelitian ini dilatarbelakangi oleh rendahnya keterampilan komunikasi matematika siswa dan kurangnya berbagai bahan ajar yang dapat membekali siswa untuk menghadapi tantangan abad ke-21 termasuk kegiatan untuk mendukung keterampilan komunikasi matematika. Penelitian ini bertujuan untuk: (1) menghasilkan Lembar Kerja Siswa matematika (LKS) dengan pendekatan STEM yang mendukung keterampilan komunikasi matematika siswa SMP dan cocok untuk digunakan dalam pembelajaran matematika. Penelitian pengembangan ini dilakukan dengan mengadopsi model penelitian dan pengembangan ADDIE. Hasil penelitian menunjukkan bahwa: (1) LKS Matematika dengan Pendekatan STEM (Sains, Teknologi dan Teknik dan Matematika) layak digunakan dengan hasil tes validasi oleh para ahli dengan persentase kelayakan mencapai 84,77% berada pada interval   4,20 yaitu 4,23 dengan kategori sangat baik; dan kualitas LKS berdasarkan respons siswa dan guru menunjukkan kriteria praktek dengan nilai persentase sebesar 75% dan 85%.